Efficiency of Acerophagus papayae on different host stage combinations of papaya mealybug, Paracoccus marginatus - Mastoi, Muhammad Ishaque; Adam, Nur Azura; Muhamad, Rita; Abd Ghani, Idris; Ahmed Gilal, Arfan; Khan, Javed; Bhatti, Abdul Rauf; Zia, Ahmed; Sahito, Jam Ghulam Mustafa (Pakistan Association of Advancement in Agricultural Sciences, 2018)
Acerophagus papayae is a koinobiont endoparasitoid of the invasive papaya mealybug, Paracoccus marginatus and has been introduced as a classical bio-control agent of the mealybug in many countries. Considering the importance, parasitism efficiency of A. papayae against various life stages of P. marginatus was conducted in choice experiments. Results suggested that A. papayae showed higher parasitism efficiency towards third instar female nymphs and adult female P. marginatus in comparison to second instar male. However, second instar male nymphs were more preferred in comparison to second instar female nymphs. Acerophagus papayae exhibited a highly significant sex-biased development ratio as a female dominant progeny emerged while feeding on female hosts and vice versa. No difference was recorded in the developmental time of male and female A. papayae, however, females matured one day later than males. The only gregarious behaviour of A. papayae was recorded on adult female P. marginatus as more than one adult parassitoid emerged from a single host. Study results suggested that A. papayae has a tremendous potential to be utilized in classical biological control programs against P. marginatus as it showed more preference towards female hosts; hence not only reducing available pest population but also will affect the pest population of next generation.